Case report: An unusual case of multisite embolism in a patient with adenovirus pneumoniae - Mao, Jia-Yu; Zhao, Hua; Cui, Na (Frontiers in Medicine, 2022)
A 36-year-old previous healthy man presented with fever, cough and dyspnea associated with adenovirus pneumonia. The patient developed left ventricular thrombus, pulmonary embolism and multisite embolism of undetermined etiology. Adenovirus is a rare cause of thrombotic events in immunocompetent individuals, calling for further studies for early diagnosis and management.